Efectividad de la ultrasonografía incorporada al score Alvarado, comparada al protocolo estándar del Hospital Regional Docente de Trujillo en el diagnóstico de apendicitis aguda: Effectiveness of ultrasonography incorporated to score Alvarado, compared to standard protocol of Trujillo Regional Teaching Hospital, in the diagnostic of acute appendicitis - Sagástegui-Aguilar, Bruno (2023)
Objetive: To determine whether ultrasound evaluation incorporated into the Alvarado score improves diagnostic accuracy for acute appendicitis, compared to the standard protocol used at Trujillo Regional Teaching Hospital (HRDT). Methods: We included 140 patients admitted to the emergency room because of abdominal pain and with suspected acute appendicitis during years 2009 and 2010. These were divided into 2 groups according to whether they underwent ultrasonography plus Score Alvarado (intervention group, IG) or the standard HRDT protocol (control group; CG). Results: In the IG, the sensitivity was 99.2%, the specificity was 71.4%, the positive predictive value was 98.5%, the negative predictive value was 83.3%, the positive likelihood ratio was 3.47 and the negative likelihood ratio was 0.01. In the CG, sensitivity was 93.1%, specificity was 55.6%, positive predictive value was 96.8%, negative predictive value was 35.7%, positive likelihood ratio was 2.10 and negative likelihood ratio was 0.12. Conclusion: Incorporating ultrasonography into the Score Alvarado appears to be an effective alternative for the diagnosis of appendicitis compared to the standard HRDT protocol.